2012
DOI: 10.1111/j.1476-5381.2012.02045.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of PAC1 and VPAC receptor subtypes elicits differential physiological responses from sympathetic preganglionic neurons in the anaesthetized rat

Abstract: BACKGROUND AND PURPOSEPituitary adenylate cyclase-activating polypeptide (PACAP) is an excitatory neuropeptide with central and peripheral cardiovascular actions. Intrathecal PACAP increases splanchnic sympathetic nerve activity and heart rate, but not mean arterial pressure (MAP). We hypothesize that the three PACAP receptors (PAC1, VPAC1 and VPAC2) have different actions in central cardiovascular control, and that their summed effect results in the lack of MAP response observed following intrathecal PACAP in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
(61 reference statements)
1
9
0
Order By: Relevance
“…Intrathecal administration, on the other hand, may activate PACAP receptors on sympathetic preganglionic neurons as well as inhibitory interneurons (47) or neurons in the dorsal and ventral horns (47) within the spinal cord. Finally, the receptor complement present on RVLM neurons compared with spinal cord neurons, and the effect of activating them, may be different in the two regions (27). While this is the first study to microinject PACAP into the RVLM, the pressor response observed is in agreement with other studies that administered PACAP centrally using other approaches (13,31,33,56).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Intrathecal administration, on the other hand, may activate PACAP receptors on sympathetic preganglionic neurons as well as inhibitory interneurons (47) or neurons in the dorsal and ventral horns (47) within the spinal cord. Finally, the receptor complement present on RVLM neurons compared with spinal cord neurons, and the effect of activating them, may be different in the two regions (27). While this is the first study to microinject PACAP into the RVLM, the pressor response observed is in agreement with other studies that administered PACAP centrally using other approaches (13,31,33,56).…”
Section: Discussionsupporting
confidence: 80%
“…PACAP acting at receptors in the spinal cord has effects on MAP (33) that vary in different strains but that do not contribute to the hypertension of the spontaneously hypertensive rat (SHR) (16). These variable effects on MAP may possibly be due to differences in PAC 1 versus vasoactive intestinal peptide receptor (VPAC) expression in the spinal cord (27). Here, we investigated a role for PACAP in the RVLM in normotension and hypertension.…”
mentioning
confidence: 99%
“…Whereas AIH causes sympathoexcitation without any change in blood pressure, experimental CIH – a well-established model for sleep apnoea – causes hypertension which is accompanied by increased noradrenaline release from the adrenal medulla (Kumar et al, 2006). In this respect, we note that a high dose of intrathecal PACAP can elevate blood pressure directly by activating PAC1 receptors on SPN innervating noradrenaline-secreting adrenal medulla chromaffin cells (Inglott et al, 2012) and that PACAP knockout mice, a proposed model of Sudden Infant Death Syndrome (SIDS) with blunted cardiorespiratory responses to hypoxia (Cummings et al, 2004), also have reduced TH expression (Arata et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Intrathecal infusion of 1 mM PACAP-38 causes large, long lasting sympathoexcitation without any change in blood pressure (Farnham et al, 2008), similar to that seen after AIH. PACAP acts at 3 receptors, PAC1, VPAC1, and VPAC2, and can differentially regulate blood pressure by activating either PAC1 or VPAC receptors in the spinal cord (Inglott et al, 2012). PACAP is closely associated with catecholaminergic regions and is rate-limiting for the release of catecholamines from the adrenal medulla during prolonged stress (Stroth et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, modulation of TNF-α should be an neuroprotective effects linked to a decrease of neuronal apoptosis and a reduction of inflammation. However, besides its neuroprotective effects, it has also been reported that PACAP, through VPAC2 receptor activation, can generate adverse effects such as hypotension, water retention, and tachycardia (Deguil et al, 2010;Farnham et al, 2011;Inglott et al, 2012;Mirfendereski et al, 1997;Tsutsumi et al, 2002;Warren et al, 1992). Also, it has been shown that a VPAC2 agonist exerts deleterious effects in a stroke model (Darsalia et al, 2013).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%